2000
DOI: 10.4049/jimmunol.164.10.5088
|View full text |Cite
|
Sign up to set email alerts
|

κ-Opioid Regulation of Thymocyte IL-7 Receptor and C-C Chemokine Receptor 2 Expression

Abstract: Endogenous and exogenous κ-opioid agonists have been widely reported to modulate the immune response. We have published results that show that the superantigen-induced proliferative response of thymocytes is inhibited by the selective κ-opioid agonist trans-3,4-dichloro-N-methyl-N-[2-(1-pyrolidinyl)cyclohexyl]benzeneaceamide methanesulfonate (U50,488H). Previous work has established that the κ-opioid receptor is widely expressed within the thymus; however, little is known about the role of the κ-opioid recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…We have reported results from studies in mice which showed that treatment with U50,488H results in an increase in CCR2 expression by developing T cells in the thymus [60]. This is in contrast to our preliminary experiments which show that activation of the KOR in human PBMCs suppresses the expression of both CCR5 and CXCR4.…”
Section: Effects Of Opioids On Chemokine Receptor Expressioncontrasting
confidence: 55%
See 1 more Smart Citation
“…We have reported results from studies in mice which showed that treatment with U50,488H results in an increase in CCR2 expression by developing T cells in the thymus [60]. This is in contrast to our preliminary experiments which show that activation of the KOR in human PBMCs suppresses the expression of both CCR5 and CXCR4.…”
Section: Effects Of Opioids On Chemokine Receptor Expressioncontrasting
confidence: 55%
“…In an effort to further examine the role of the KOR in the function of developing T cells in the thymus, we have tested the impact of U50,488H administration on the expression of cytokines and cytokine receptors in superantigen-stimulated thymocytes by RNase-protection analysis (RPA) [60]. We have measured detectable levels of the cytokines IL-2, IL-4, IL-5, IL-13 and IFNγ, and the chemokines lymphotactin and RANTES in stimulated thymocyte cultures; however, addition of U50,488H did not alter the expression of these cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Oligomerization of mu, kappa and delta opioid receptors with the chemokine receptor CCR5 on the cell membrane of human or monkey lymphocytes has been reported and suggests that opioid receptors interact with CCR5 in cells coexpressing both receptors (Suzuki et al, 2002). The kappa opioid receptor has been shown to regulate thymocyte C-C Chemokine receptor 2 expression (Zhang and Rogers 2000) and a kappa agonist inhibits monocyte chemoattractant protein-1 (CCL2) production by human astrocytes (Sheng et al, 2003) and SDF-1alpha receptor CXCR4 expression on CD4+ lymphocytes (Lokensgard et al, 2002). In addition, unpublished data from our collaborators indicate the co-localization of both opioid and chemokine receptors in several brain areas, including PAG (L. Kirby, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hormone-mediated "indirect" modulation of cell proliferation, opioids modify T-and B-cell responses (Guan et al, 1997;Shahabi et al, 2000;Beagles et al, 2004;Roy et al, 2004), macrophage and microglial activity (Belkowski et al, 1995;Hu et al, 2000;Hu et al, 2002), chemotaxis (Szabo et al, 2002), cell migration (Patel et al, 2003), and natural killer cell cytotoxicity (Hsueh et al, 1996;Boyadjieva et al, 2001;Yeager et al, 2002) by modifying cytokine and chemokine release (Belkowski et al, 1995;Alicea et al, 1996;Kong et al, 1997;Wetzel et al, 2000b;Sacerdote, 2003), respective receptor expression (Zhang and Rogers, 2000), and chemokine receptor responsiveness (Grimm et al, 1998a;Rogers et al, 2000;Szabo et al, 2002Szabo et al, , 2003Chen et al, 2004) (for review, see McCarthy et al, 2001 and. These effects do not necessarily affect survival of the opioid-stimulated cell but may modify the course of inflammatory and infectious diseases, such as HIV infection, and thereby survival of the organism.…”
Section: B Chemokine-and Cytokine-mediated Effectsmentioning
confidence: 99%